Tablet Apps and Dexterity: Comparison Between 3 Age Groups and Proof of Concept for Stroke Rehabilitation. Issue 1 (January 2016) - Kizony, Rachel; Zeilig, Gabi; Dudkiewicz, Israel; Schejter-Margalit, Tamara; Rand, Debbie
Abstract : Background and Purpose: Touch screen tablet technology might be suitable for self-training of impaired dexterity poststroke. We compared performance of app-based hand activities in individuals without a disability from 3-age groups, and assessed the feasibility of using tablet apps in individuals with stroke. Methods: Experiment I included 172 Individuals without a disability: 79 young adults (26.2 [3.9] years old), 61 middle-aged adults (55.9 [5.1] years old), and 32 older adults (68.7 [3.0] years old). Experiment II included 20 individuals with stroke, aged 59.3 ± 13.7 years with impairment of the upper extremity. All participants performed the app-based "Tap-it" (tapping) task twice and the Nine Hole Peg Test. The stroke group practiced with additional apps and underwent clinical assessments. Results: Significant differences in the tapping task performance were found between the 3 age groups (dominant hand time: F(2, 169) = 30.57; P = 0.0001; and accuracy F(2, 169) = 25.20; P = 0.0001; nondominant hand time: F(2, 169) = 35.09; P = 0.0001; and accuracy F(2, 169) = 19.62; P = 0.0001). Of the 20 individuals with stroke, 15 were able to complete the 2 trials of the tapping task, but all participants reported enjoying the experience and thought the apps may have potential for stroke rehabilitation to improve performance of the stroke-affected hand. Discussion and Conclusions: Performance of tablet app-based hand activities was affected by impaired hand dexterity in older participants without a disability and in participants with stroke. Tablet apps may potentially provide a way to facilitate self-training of repetitive, task-oriented, isolated finger and hand movements to improve hand dexterity and function after stroke. Video abstract available for additional insights from the authors (see Supplemental Digital Content 1, http://links.lww.com/JNPT/A118 ). Abstract : Supplemental Digital Content is Available in the Text.